Comprehensive treatment of cervical dysplasia from moderate to severe degree on the HPV infection background - Yu E Dobrohotova; M G Venediktova; I I Grishin; A N Sarantsev; K V Morozova; N N Lutsenko (IP Berlin A.V., 2015)
The article is devoted to an actual problem of modern health care is the treatment and prevention of cervical dysplasia. In recent years, despite the development of science and medicine has continued to increase the incidence of precancer and cancer of the cervix, which necessitated the creation of newand improvement of existing methods of diagnosis and treatment of precancerous diseases of the cervical epithelium. According to many researchers in a large percentage of cases of this pathology has a viral etiology and due carriage of HPV (human papilloma virus) high-risk types. The currently existing immunomodulators suppress the activity of HPV, thereby reducing the risk of pathological changes in the cervical epithelium. One of these drugs with proven efficacy is Isoprinosine. Given the urgency of this problem, it is necessary to further study and selection of schemes of immunomodulators, evaluation of their effectiveness in terms of clinical outcomes with the aim of reducing the risk of developing dysplasia moderate and severe and cervical cancer, on the background of carrying HPV.